PENGARUH KINERJA PERSONEL GROUND HANDLING PT. KOKAPURA DALAM MENANGANI ARRIVAL BAGGAGE TERHADAP TINGKAT KEPUASAN PENUMPANG DI BANDAR UDARA INTERNASIONAL JENDERAL AHMAD YANI SEMARANG - Salsabella Indah Widatin Ningrum; Abdul Mu’ti Sazali; Yuyun Suprapto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Ground handling agents assist airline companies in all aircraft operational matters during the pre-flight and post-flight phases, this affects the level of passenger satisfaction in using flight services. The purpose of this study is to determine how satisfied passengers are with the services provided by the airline through ground handling at the time of arrival. The object of this research is airplane passengers that are shaded by Ground Handling PT. Kokapura by taking 400 passenger samples. Land Handling PT. Kokapura handles aircraft operational services including Lion Air, Batik Air, Wings Air, Sriwijaya Air, and Nam Air. The research method uses quantitative methods where the research carried out obtains data in the form of numbers which are then obtained and processed using statistical applications in the form of SPSS and Minitab. Data collection techniques used observation techniques, questionnaires, literature studies and research instruments. Methods of data collection using the method of observation, questionnaires, and literature study. The final results achieved from this study indicate that the performance of ground handling personnel affects the level of passenger satisfaction in addition to passenger satisfaction which is also influenced by the services provided by ground handling to passengers. The research that has been done has obtained results that show that the performance of ground handling personnel at PT. Kokapura affects the level of passenger satisfaction by 45.4%. Meanwhile, influence other factors outside the study.